Design of rigid structures for wind using time series of demand-to-capacity indexes: Application to steel portal frames. (1st February 2017) - Habte, Filmon; Chowdhury, Arindam Gan; Yeo, DongHun; Simiu, Emil
Highlights: Direct computation of Demand-to-Capacity Indexes of structural members. Automatic, rigorous combination of imperfectly correlated time series of wind effects. Due to suppression of loading information ASCE 7 Standard is in many cases unconservative. Abstract: Estimates of wind effects on rigid buildings by database-assisted design (DAD) methods can be far more accurate than those based on information available in standards. An upgraded version of DAD is presented that streamlines the wind engineering/structural engineering components of the design process by allowing the direct computation of Demand-to-Capacity Indexes (DCIs). The computation achieves the rigorous combination of imperfectly correlated time series of wind forces and effects, thus eliminating errors due to subjective estimates of combined effects. The basic approach being presented is applicable to any rigid building. This paper focuses on simple buildings with gable roofs, portal frames, and bracing parallel to the ridge. Useful features of this work include: the capability to use the two largest building aerodynamics databases available worldwide; the use of large simulated extreme wind databases for hurricane- and non-hurricane-prone regions; a novel interpolation scheme allowing the design of buildings with dimensions not represented in the databases; an effective multiple-points-in-time algorithm for estimating peaks; and parameter-free methods for estimating DCIs with specified mean recurrence intervals. Case studies indicated that the proposed interpolation scheme was satisfactory. The results obtained confirm: (i) published results which show that the ASCE 7-10 envelope procedure can significantly underestimate wind effects; (ii) the mutual consistency for practical purposes of the two aerodynamic databases being used; and (iii) DAD's potential for practical use in structural design. The software developed for the implementation of the procedure is available athttp://www.itl.nist.gov/div898/winds/iterative_design/wind_design.htm . A user's manual is available athttp://nvlpubs.nist.gov/nistpubs/TechnicalNotes/NIST.TN.1908.pdf .